2017
DOI: 10.5578/tt.66324
|View full text |Cite
|
Sign up to set email alerts
|

Which factors effects patients belief and attitudes about influenza vaccination?

Abstract: The vaccination rate remains low. Opinions about the vaccine that had favourable effect on vaccination rate were that the vaccine was beneficial and that it would protect one's family against the disease. The unvaccinated patients had inadequate knowledge of the vaccine. Obtaining information from a physician boosts vaccination rate. Men having a greater rate of vaccination through campaigns of workplaces as well as a greater rate of being informed can be explained by a higher employment rate in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Studies investigating COVID-19 vaccine attitudes demonstrated similar results (Dror et al, 2020;Papini et al, 2022). This finding is confirmed by studies (Çiftci et al, 2017;Reda Alenazi et al, 2018) revealing higher flu vaccine uptake among physicians and conducted worldwide, including two meta-analyses where the prevalence of the influenza vaccine among physicians was 23.18% (Mannocci et al, 2010), 13.47% among nurses, and 12.52% among other healthcare professionals (La Torre et al, 2011). In this regard, two studies in the literature on other vaccines (Bianchi et al, 2022;Ledda et al, 2021) agree that physicians with higher education levels and higher rates of using scientific resources display better compliance with vaccination.…”
Section: Discussion Of Sociodemographic Factorssupporting
confidence: 64%
“…Studies investigating COVID-19 vaccine attitudes demonstrated similar results (Dror et al, 2020;Papini et al, 2022). This finding is confirmed by studies (Çiftci et al, 2017;Reda Alenazi et al, 2018) revealing higher flu vaccine uptake among physicians and conducted worldwide, including two meta-analyses where the prevalence of the influenza vaccine among physicians was 23.18% (Mannocci et al, 2010), 13.47% among nurses, and 12.52% among other healthcare professionals (La Torre et al, 2011). In this regard, two studies in the literature on other vaccines (Bianchi et al, 2022;Ledda et al, 2021) agree that physicians with higher education levels and higher rates of using scientific resources display better compliance with vaccination.…”
Section: Discussion Of Sociodemographic Factorssupporting
confidence: 64%
“…A study conducted in Turkey found that 33.4% and 9.9% of patients having indications for vaccination are vaccinated for influenza and PN vaccine, respectively [ 20 ]. Although PN vaccine has been available in Turkey since 1994 and reimbursed by the government for high-risk group since 2007, the vaccination rate was found to be low at only 2% in elderly and adults at high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Advisory Committee on Immunization Practices recommends universal annual influenza vaccinations for all individuals aged ≥6 months (3). The influenza vaccination not only reduces the risk of influenza infection but also reduces the severity of the illness in those who are infected (4,5). The Turkish Ministry of Health recommends and supplies free influenza vaccines to a wide range of individuals, including pregnant women; individuals aged ≥65 years; children aged 6 months to 2 years; residents of nursing homes and other chronic-care facilities; individuals who suffer from chronic pulmonary (including asthma), cardiovascular, renal, hepatic, neurologic, hematologic, or metabolic disorders [including diabetes mellitus (DM)]; individuals with obesity; health care personnel; and individuals aged 6 months to 18 years and receiving long-term aspirin therapy.…”
Section: Introductionmentioning
confidence: 99%